Truth sacrificed as academic neutrality on Gaza plagues scholarly discourse - Mohamad Jamil, Siti Nurnadilla (TRT World, 2024)
Academics at influential universities are making a conscious choice of adopting neutrality on Palestine, reinforcing the brutal occupation of Israel, including the perpetuation of ‘genocide’ in broad daylight.